Sugar, a powerful substitute for ethanol in ethanol postdependent rats: Relevance for clinical consideration?. (8th February 2021) - Alaux‐Cantin, Stéphanie; Alarcon, Régis; Audegond, Clément; Simon O'Brien, Emmanuelle; Martinetti, Margaret P.; Ahmed, Serge H.; Nalpas, Bertrand; Perney, Pascal; Naassila, Mickael
Abstract: Sugar has been shown to be a powerful substitute for drugs in preclinical studies on addiction. However, the link between sugar intake and alcohol use disorder (AUD) is poorly understood. We assessed the influence of sucrose on ethanol drinking in both nondependent (ND) and dependent (D) Long–Evans rats during acute withdrawal using the postdependent state model. Ethanol (10%–40%) and sucrose (1%–4%) solutions were offered in an operant paradigm either independently or concurrently under ratio schedules of reinforcement. We showed that D rats displayed an enhanced motivation for both 10% ethanol solution (10E) and 4% sucrose solution (4S) as compared with ND rats, and a clear preference for 4S was observed in both groups. During acute withdrawal, D rats showed a strong motivation for 30% ethanol (30E), even when adulterated with quinine, but still preferred 4S despite the fact that a high level of negative reinforcement could be expected. However, when a premix solution (30E4S) was offered concurrently with 4S, the preference for 4S was lost in D animals, which consumed as much premix as 4S, whereas ND animals displayed preference for 4S. Altogether, those results suggest that reinforcing properties of sucrose surpass those of ethanol in D rats under acute withdrawal, which indicates that sugar is a powerful substitute for ethanol. Our results suggest that craving for sugar may be increased in AUD patients during withdrawal and raise the issue of dependence transfer from alcohol to sugar. Abstract : Ethanol‐dependent rats showed a strong motivation for the 30% ethanol solution, even adulterated with quinine. The preference for sugar is not seen in dependent animals when a premix (sugar and ethanol) is offered. Reinforcing properties of sucrose surpass those of ethanol in ethanol‐dependent rats under acute withdrawal, making sugar a powerful substitute for ethanol.